Relação peso-comprimento e fator de condição de Brycon opalinus (Pisces, Characiformes) no Parque Estadual da Serra do Mar-Núcleo Santa Virgínia, Mata Atlântica, Estado de São Paulo, Brasil - Gomiero, Leandro Muller [UNESP]; Braga, Francisco Manoel de Souza [UNESP] (Universidade Estadual de Maringa, 2006)
In this study, the length-weight relationship and the condition factor of Brycon opalinus were analyzed in three rivers within the Santa Virgínia Unit, at Serra do Mar State Park, in São Paulo State. The different conditions in these three environments were evidenced, such as the seasonality, reproductive period, and the differences between females and males according to the parameters which evidenced the best physiological condition of the fish. In this species, the condition factor varied along the seasons at all three collection sites. The length of the first gonadal maturation and the reproductive period were long, with the highest intensity in the spring and summer.
Length-weight relationship and condition factor for Brycon opalinus (Pisces, Characiformes) in Serra do Mar State Park - Santa Virgínia Unit, Atlantic Forest, São Paulo State, Brazil
Keywords: Brycon opalinus; Condition factor; Length-weight relationship; Brazil; controlled study; environmental factor; female; fish; gonad development; male; nonhuman; physiology; reproduction; river; seasonal variation; spring; summer; Characiformes; Pisces